THE DYNAMICS OF CHINESE FOREIGN POLICY THROUGH THE PRISM OF NATIONAL INTERESTS - M. Yu. Korostikov (Сравнительная политика, 2016)
The article is devoted to the analysis of the dynamics of China's foreign policy through the prism of understanding the changes in its national interests as understood by the Chinese leadership. It includes a brief description of the approaches to the analysis of the national interests by Western authors and its comparison with the Chinese tradition. Analysis of China's foreign policy changes during the transition from the fourth to the fi fth generation of Chinese leaders is given through the tenets of the Chinese international relations scholar Yan Xuetong theory. The main conclusion of the article is that the recent assertiveness of the Chinese foreign policy is the result of country’s successes in achieving economic goals, which made it possible to shift priorities from providing economic growth to conquering the leading position in the world.